Graduate Social Work Students' Knowledge, Attitudes, and Beliefs About Medical Marijuana. (2nd October 2022) - Findley, Patricia A.; Isralowitz, Richard; Reznik, Alexander
ABSTRACT: Perceptions of medical marijuana (MM) use have changed, particularly around its value for chronic illnesses/related symptoms. Social workers are open to questions from clients about use and efficacy of MM. Aims of this study are to assess knowledge and attitudes about MM among graduate social work students. Of the 230 respondents, 88.7% were female. Over half of the students did not report MM posed any physical/mental health risk for clients. We found a strong belief in the value of MM among those with limited reliance on formal information sources. We found respondents lacked preparedness to address client needs around MM. Study findings contribute to identifying key issues linked to possible social work curriculum and policy development for MM education/practice purposes.